Share
Explore BrainMass

2 Objective questions

Please choose the correct answer:

∫ 12x(x - 2)^10 dx =

x^12 + (24/11)x^11 + C
x^12 + (2/11)x^11 + C
(12/11)(x - 2)^11 + C
(12/11)x(x - 2)^11 + c
(x - 20/11)(x - 2)^11 + C
(x + 2/11)(x - 2)^11 + C
none of these

b b c c
Given that ∫ x^2 dx = 5, ∫ x^5 dx = 3, ∫b x^2 dx = 5/2, and ∫b x^5 dx = 4/3,
a a
a
then ∫c (2x^2 - 3x^5) dx =

- 41/6
- 4
- 2
2
4
41/6
none of these

Solution Preview

17. ∫ 12x(x - 2)^10 dx =

x^12 + (24/11)x^11 + C
x^12 + (2/11)x^11 + C
(12/11)(x - 2)^11 + C
(12/11)x(x - 2)^11 + c
(x - 20/11)(x - 2)^11 + C
(x + 2/11)(x - 2)^11 + C
none of these

The answer is "none of these", you can check by ...

$2.19